2022
DOI: 10.1111/jbi.14341
|View full text |Cite
|
Sign up to set email alerts
|

PAICE: A new R package to estimate the number of inter‐island colonizations considering haplotype data and sample size

Abstract: Aim: Colonization is a central topic in ecology and one of the cornerstones of island biogeography. Although the evolutionary history of island species is widely studied, the quantification of colonization is particularly challenging because the same area may be colonized multiple times by the same species, whereas initially successful colonization events may eventually be followed by extinction. Nevertheless, an estimation of the actual number of within-archipelago colonization events can be achieved when usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(32 citation statements)
references
References 57 publications
0
32
0
Order By: Relevance
“…Finally, we used the argument method = 1 to allow the algorithm to fit the accumulation curve of colonization events with fewer parameters if curves could not be fitted initially. As the outgroup was connected to E. canariensis at two points (two missing haplotypes between haplotypes A and B; see Results), we repeated the analysis considering each of these possible ancestral haplotypes (see Coello et al, 2022 for additional information).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Finally, we used the argument method = 1 to allow the algorithm to fit the accumulation curve of colonization events with fewer parameters if curves could not be fitted initially. As the outgroup was connected to E. canariensis at two points (two missing haplotypes between haplotypes A and B; see Results), we repeated the analysis considering each of these possible ancestral haplotypes (see Coello et al, 2022 for additional information).…”
Section: Methodsmentioning
confidence: 99%
“…Given the occurrence of this species in the six major islands of the Canarian archipelago (considering Lanzarote and Fuerteventura as the single palaeoisland of Mahan; Troll and Carracedo, 2016), E. canariensis has experienced at least five inter-islands colonization events based on chorology alone (Arjona et al, 2018;Vargas et al, 2015). The geographic distribution of plastid DNA diversity (Figure 3) indicates a minimum of eight colonization events, and estimates obtained in PAICE considering sampling effort (Coello et al, 2022) suggested c. 20 -50 colonization events (see Results, Figure 4). Results of this study corroborate results of Coello et al (2022) regarding the fact that DPA analysis (c. 13 colonization events with a 95% confidence interval of 9 -19 colonization events) estimates a smaller number of inter-island colonization events than PAICE.…”
Section: Colonization Ability Of E Canariensismentioning
confidence: 99%
See 3 more Smart Citations